Analyzing Consumer Purchasing Behavior Through Economic Lens: The Effect of Location and Service Quality At Point Coffee, Medan - Gultom, Pesta; Nainggolan, Elisabeth; Monica, Cencen (Yayasan Riset dan Pengembangan Intelektual, 2025)
Point Coffee Indomaret Fresh, located in the Gedung Arca area of Medan, operates in the food and beverage (F&B) sector and currently faces challenges in increasing sales and maintaining market competitiveness. Despite being the only coffee shop in the area, its strategic location appears suboptimal, with limited visibility and accessibility for potential customers. In addition, inadequate service quality has negatively impacted customer satisfaction, contributing to declining consumer purchasing behavior. This study analyzes the economic impact of location and service quality on consumer purchasing decisions at Point Coffee through a quantitative approach. The research population includes all customers of Point Coffee Gedung Arca Medan. Due to the unknown total population, Hair et al.’s (2010) sampling formula is applied, using a maximum multiplier of 10 per indicator across all variables, resulting in a total sample of 90 respondents. The findings reveal that both location and service quality significantly influence consumer purchasing decisions, both individually and jointly. These results underscore the importance of strategic location planning and consistent service improvement in enhancing economic performance and customer retention in competitive retail-based F&B businesses.